2020
DOI: 10.7717/peerj.9354
|View full text |Cite
|
Sign up to set email alerts
|

A putative effector UvHrip1 inhibits BAX-triggered cell death in Nicotiana benthamiana, and infection of Ustilaginoidea virens suppresses defense-related genes expression

Abstract: Rice false smut (RFS), caused by Ustilaginoidea virens, is one of the most detrimental rice fungal diseases and pose a severe threat to rice production and quality. Effectors in U. virens often act as a set of essential virulence factors that play crucial roles in the interaction between host and the pathogen. Thus, the functions of each effector in U. virens need to be further explored. Here, we performed multiple alignment analysis and demonstrated a small secreted hypersensitive response-inducing protein (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Two putative orthologues of CSEP genes that have previously been implicated in pathogenicity were present in Gt and Ga pathogenic taxa but missing in non-pathogenic Gh , making them promising targets for future experiments to determine if either is important for Gt pathogenicity in wheat. UvHrip1 (from Ustilaginoidea virens ) is thought to be involved in suppressing host immunity and has already been reported in Gt (Wang et al 2020), while PBC1 (from Pyrenopeziza brassicae ) is a cutinase implicated in host penetration (Li et al 2003). It was intriguing that none of the CSEPs assigned to PHI-base genes were unique to Gt , perhaps suggesting that there is relatively high overlap in effector-mediated virulence mechanisms in Gt and Ga .…”
Section: Discussionmentioning
confidence: 99%
“…Two putative orthologues of CSEP genes that have previously been implicated in pathogenicity were present in Gt and Ga pathogenic taxa but missing in non-pathogenic Gh , making them promising targets for future experiments to determine if either is important for Gt pathogenicity in wheat. UvHrip1 (from Ustilaginoidea virens ) is thought to be involved in suppressing host immunity and has already been reported in Gt (Wang et al 2020), while PBC1 (from Pyrenopeziza brassicae ) is a cutinase implicated in host penetration (Li et al 2003). It was intriguing that none of the CSEPs assigned to PHI-base genes were unique to Gt , perhaps suggesting that there is relatively high overlap in effector-mediated virulence mechanisms in Gt and Ga .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that pathogen infection induces SWEET expression, which enhances host susceptibility [11] , while the effectors secreted by pathogen induce the expression of host defense genes. For example, the secretion of hypersensitive response-inducing protein 1(UvHrip1) by the pathogen into rice downregulated OsPR expression [12] . In addition, TAL effectors, delivered to the plant cytoplasm through the type III secretory system, induced the expression of specific SWEET genes, ensuring sucrose delivery to the apoplasts of colonized cells [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Rice false smut caused by U. virens has become one of the most serious diseases, which not only affects the yield and quality of rice but also produces a large number of rice false smut balls . These balls are often rich in mycotoxins, such as ustilaginoidins, ustiloxins, and sorbicillinoids, which decreases rice production.…”
Section: Introductionmentioning
confidence: 99%